Beyond the Pandemic: Last-Mile Teachers’ Insights for Future-Ready Education in Rural Schools - Villamor, Sonny (Lavai - International Journal of Education, 2025)
Modular Distance Learning (MDL) became a critical mode of instruction during the COVID-19 pandemic, especially in remote schools with limited access to technology and internet connectivity. In this context, learners independently complete lessons using printed self-learning modules, while teachers are responsible for preparing, distributing, and retrieving these materials. This study explores the lived experiences of the last-mile teachers regarding the implementation of MDL in a public secondary school located in a remote community. Using a phenomenological research design, the study captured the lived experiences of 15 teachers selected through purposive and convenience sampling based on their involvement in MDL. In-depth interviews served as the primary data collection method, and thematic analysis was used to identify recurring patterns and insights. The findings reveal a complex view of MDL, with teachers recognizing both its advantages, such as flexibility and learner autonomy, and its disadvantages, including time-consuming preparation and limited resources. Key challenges included difficulties in monitoring student progress, engaging parents, and managing inconsistent work arrangements. To cope, teachers employed action-based strategies, such as home visitations, and emotion-based strategies, such as maintaining a positive outlook and offering emotional support. The study offers recommendations to enhance MDL implementation, including strengthening teacher support, fostering greater parental involvement, and improving training and resource allocation. The study concludes that while MDL has shown potential as a solution during crises, its future success depends on community-wide support, improved logistical coordination, and policies that are adaptable to the evolving needs of educators and students in remote contexts.